Mission design of DESTINY+: Toward active asteroid (3200) Phaethon and multiple small bodies. (July 2022) - Ozaki, Naoya; Yamamoto, Takayuki; Gonzalez-Franquesa, Ferran; Gutierrez-Ramon, Roger; Pushparaj, Nishanth; Chikazawa, Takuya; Tos, Diogene Alessandro Dei; Çelik, Onur; Marmo, Nicola; Kawakatsu, Yasuhiro; Arai, Tomoko; Nishiyama, Kazutaka; et al.
Abstract: DESTINY + is an upcoming JAXA Epsilon medium-class mission to fly by the Geminids meteor shower parent body (3200) Phaethon. It will be the world's first spacecraft to escape from a near-geostationary transfer orbit into deep space using a low-thrust propulsion system. In doing so, DESTINY + will demonstrate a number of technologies that include a highly efficient ion engine system, lightweight solar array panels, and advanced asteroid flyby observation instruments. These demonstrations will pave the way for JAXA's envisioned low-cost, high-frequency space exploration plans. Following the Phaethon flyby observation, DESTINY + will visit additional asteroids as its extended mission. The mission design is divided into three phases: a spiral-shaped apogee-raising phase, a multi-lunar-flyby phase to escape Earth, and an interplanetary and asteroids flyby phase. The main challenges include the optimization of the many-revolution low-thrust spiral phase under operational constraints; the design of a multi-lunar-flyby sequence in a multi-body environment; and the design of multiple asteroid flybys connected via Earth gravity assists. This paper shows a novel, practical approach to tackle these complex problems, and presents feasible solutions found within the mass budget and mission constraints. Among them, the baseline solution is shown and discussed in depth; DESTINY + will spend two years raising its apogee with ion engines, followed by four lunar gravity assists, and a flyby of asteroids (3200) Phaethon and (155140) 2005 UD. Finally, the flight operations plan for the spiral phase and the asteroid flyby phase are presented in detail. Highlights: Mission design and space flight operations of JAXA's DESTINY + mission is introduced. A novel approach to tackle complex low-thrust trajectory design is proposed. Low-thrust many-revolution trajectory design approach is presented. High-fidelity moon flyby database is utilized to patch the entire trajectory. A new asteroid flyby cycler method is applied for Phaethon flyby trajectory design.